(untitled) - New, Michael B. (Bombay, 1994)
The AADCP covers research, training and information aspects of marine fish and shrimp nutrition, fish and crustacean genetics, aquaculture technology verification and improvement, development of lakes and revervoirs for fish production, and the methology of brackishwater aquaculture site selection linked with the monitoring of its ecological and socio-economic impact.
Keywords: Freshwater prawn farming,Shrimp culture